Endoscopic Versus Surgical Therapy for Early Esophagogastric Junction Adenocarcinoma Based on Lymph Node Metastasis Risk: A Population-Based Analysis - Ye, Hua; Chen, Ping; Wang, Yi-Fan; Cai, Xiu-Jun (Frontiers in Oncology, 2021)
Background In this study, we aimed to compare the prognosis and lymph node metastasis (LNM) risk in patients with early-stage esophagogastric junction (EGJ) adenocarcinoma after endoscopic treatment (ET) or radical surgery. Methods We collected data from eligible patients based on the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2016. Logistic regression analysis was used to determine independent predictors of LNM (examination of at least 16 lymph nodes). Cox regression analysis and propensity score-matched (PSM) analysis were subsequently utilized to compare the overall survival (OS) and cancer-specific survival (CSS) of patients treated with ET or radical surgery. Results In total, 3708 patients were identified. Among them, 856 patients had greater than or equal to 16 examined lymph nodes (LNs) (LNE≥16). The LNM rates were 18.8% in all patients 8.3% in T1a patients and 24.6% in T1b patients. Independent predictors of LNM were submucosal invasion, tumor size ≥3cm and decreasing differentiation (P<0.05). The LNM rate decreased to approximately 5.3% in T1b tumors with well differentiation and tumor size <3cm. However, the LNM incidence increased to 17.9% or 33.3% in T1a tumors with poor differentiation or with both tumor size≥3cm and poor differentiation. Cox regression analysis demonstrated CSS was not significantly different in early-stage EGJ adenocarcinoma patients undergoing ET and those treated with radical surgery (HR= 1.004, P=0.974), which were robustly validated after PSM analysis. Moreover, subgroup analysis stratified by T1a and T1b showed similar results. Conclusions The findings of this study indicated ET as an alternative to radical surgery in early EGJ adenocarcinoma.